Investigating Spinner Dolphin (Stenella longirostris) Occurrence and Acoustic Activity in the Maui Nui Region - McElligott, Megan M.; Lammers, Marc O. (Frontiers in Marine Science, 2021)
Hawaiian spinner dolphins (Stenella longirostris) rest during the day in the islands’ coastal waters where they are susceptible to human disturbance. Due to concerns over the negative impacts of human activity, the Pacific Islands Regional Office of the National Oceanic and Atmospheric Administration (NOAA) has proposed a 50-yard approach rule for spinner dolphins and is also considering time-area closures of certain important spinner dolphin resting areas. However, gaps still persist in the understanding of how spinner dolphin populations on different Hawaiian Islands use coastal waters, raising questions about the efficacy of the proposed rules. To better understand how spinner dolphins use the waters in the Maui Nui region (Maui, Moloka‘i, Lāna‘i, and the ‘Au‘au channel), a study was conducted using a combination of passive acoustic monitoring and vessel surveys to document spinner dolphin occurrence and movements. Bottom-moored acoustic recorders were deployed at eight locations in Maui Nui, and at one previously established resting bay off west O‘ahu for comparison. The amount of whistles, clicks, and burst pulses at each location was quantified and averaged by the hour of the day. Acoustic activity was greater at the O‘ahu site than at any of the Maui Nui sites, and was greatest between sunrise and noon. Acoustic activity and vessel surveys both reveal that spinner dolphins occur and exhibit resting behaviors in the ‘Au‘au channel between Maui and Lāna‘i, and also along west Maui and southeast Lāna‘i. Spinner dolphins resting in a channel between islands appears to be unique to Maui Nui and differs from resting patterns described along Hawai‘i Island and O‘ahu. Because spinner dolphins appear to use both the coastlines and the channel to rest in Maui Nui, the 50-yard approach rule appears to be a more suitable management option for the region than time-area closures.